The Improvement of CRISPR-Cas9 System With Ubiquitin-Associated Domain Fusion for Efficient Plant Genome Editing - Zheng, Xuelian; Qi, Caiyan; Yang, Lijia; Quan, Quan; Liu, Binglin; Zhong, Zhaohui; Tang, Xu; Fan, Tingting; Zhou, Jianping; Zhang, Yong (Frontiers in Plant Science, 2020)
Genome editing technology represented by CRISPR-Cas9 had been widely used in many biological fields such as gene function analysis, gene therapy, and crop improvement. Due to the complexity of the eukaryotic genome, there was still a problem that unstable editing efficiency with large variability among different target sites. It was important to further improve the editing efficiency of the CRISPR-Cas9 system among the whole genome. In this study, based on the previous single transcription unit genome editing system (STU-SpCas9), using the ubiquitin-associated domain (UBA) to enhance the stability of Cas9 protein, we constructed three Cas9-UBA fusion systems (SpCas9-SD01, SpCas9-SD02 and SpCas9-SD03). Four different target sites of rice OsPDS, OsDEP1 and OsROC5 genes were chosen to evaluate the genome editing efficiency in rice protoplasts and stable transformed rice plants. The results showed that the fusion of UBA domains did not affect the cleavage mode of Cas9 protein, and effectively increase the editing efficiency of STU-SpCas9 at the target sites. This new CRISPR-Cas9-UBA system provided a new strategy and tool for improving the genome editing efficiency of CRISPR-Cas9 in plants.